Determinants of the awareness of rabies and adoption of control measures among the dog owners of thrissur district - Soja Augustin (Department of Extension, College of Veterinary and Animal Sciences, 2008)
Determinants of the general awareness of rabies and adoption of control measures among the dog owners of Thrissur district of Kerala were studied. Dog owners’ general awareness of rabies and its control measures transcending all the domains viz. etiology and spread, symptoms, and control measures of rabies indicated that those of medium awareness predominated across all the three regions- hilly, coastal and plains. Significant regional differences were observed on general awareness of rabies and control measures. Dog owners of hilly and coastal regions as compared to plains comparatively lagged behind on general awareness and control measures. Formal education, media exposure and attitude towards humane dog rearing were associated with general awareness of rabies and its control.